Fabrication of complex shaped ceramic articles from 3D printed polylactic acid templates by replication process. Issue 15 (15th October 2019) - Mamatha, Sirisala; Biswas, Papiya; Das, Dibakar; Johnson, Roy
Abstract: Porous honeycombs of three ceramic formulations and configurations were replicated from 3D printed polylactic acid (PLA) templates. Sacrificial PLA templates were coated with ceramic slurries of optimum rheology and were subjected to fugitive thermal degradation based on the TG-DTA patterns recorded followed by sintering. Though the polymer replication process is known, 3D printed PLA templates are not explored for fabrication of ceramic complex shapes. 3D printed PLA offers flexibility to produce complex ceramic parts with structural integrity and engineered porosity. In the present study, 3D printed template replication technique has been used to demonstrate fabrication of honeycombs with relative density as low as 0.1 with porosity of 75–85% which is alo complemented by microstructural studies. Further, the samples exhibited cellular behavior under quasistatic compression with high energy absorption capabilities and moderate compressive strength of 1.5–2.2 MPa depending upon the ceramic formulations.